Diagnosis of the Static Excitation Systems of Synchronous Generators with the Use of Hardware-In-the-Loop Technologies - Andriy Kutsyk (MDPI AG, 2021)
In this paper, testing and diagnosis methods for the static excitation systems of power plant synchronous generators using Hardware-In-the-Loop technology are described. These methods allow a physical excitation system to be connected to a real-time model of a power plant unit. A feature of a static excitation system is the presence of generator self-excitation—that is, when the input voltages of the excitation system are defined by a synchronous generator. These voltages are determining by the digital model, which creates additional difficulties with combining a digital model with a real excitation system. Various ways to solve this problem are described in this article; in particular, we focus on the option in which the gate-impulses of a thyristor converter are applied to the digital model by a real static excitation system. The real-time models are based on the method of average voltages in the integration step. This method is effective for providing numerical stability for the models of power schemes and their functioning in real time mode over a long period. A synchronization method for the calculation time of the model with real time is described. The adequacy of the described method is proved by the results of the static excitation system of synchronous generators testing in operating and fault modes.